Distribution and Characteristics of Human Plague Cases and Yersinia pestis Isolates from 4 Marmota Plague Foci, China, 1950–2019 - Zhaokai He; Baiqing Wei; Yujiang Zhang; Jun Liu; Jinxiao Xi; Dunzhu Ciren; Teng Qi; Junrong Liang; Ran Duan; Shuai Qin; Dongyue Lv; Yuhuang Chen; et al. (Emerging Infectious Diseases, 2021)
We analyzed epidemiologic characteristics and distribution of 1,067 human plague cases and 5,958 Yersinia pestis isolates collected from humans, host animals, and insect vectors during 1950–2019 in 4 Marmota plague foci in China. The case-fatality rate for plague in humans was 68.88%; the overall trend slowly decreased over time but fluctuated greatly. Most human cases (98.31%) and isolates (82.06%) identified from any source were from the Marmota himalayana plague focus. The tendency among human cases could be divided into 3 stages: 1950–1969, 1970–2003, and 2004–2019. The Marmota sibirica plague focus has not had identified human cases nor isolates since 1926. However, in the other 3 foci, Y. pestis continues to circulate among animal hosts; ecologic factors might affect local Y. pestis activity. Marmota plague foci are active in China, and the epidemic boundary is constantly expanding, posing a potential threat to domestic and global public health.